Claudia Ringler on Microinsurance decisions: gendered evidence from rural Bangladesh - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Microinsurance decisions: gendered evidence from rural Bangladesh Presentation by Claudia Ringler from IFPRI at the seminar Closing the gender gap in farming under climate change held 19 March 2015 in Paris. Read more about the event: https://ccafs.cgiar.org/events/closing-gender-gap-farming-under-climate-change-new-knowledge-renewed-action